Pendampingan Peningkatan Kualitas Pengabdian Kepada Masyarakat Bagi Mahasiswa KKN ke-82 UIN Raden Fatah Palembang - Firmansyah; Erisa Ardika Prasada; Nyayu Soraya; Rohmadi; Middya Boty (Pusmedia Group Indonesia, 2025)
This community service activity aims to increase the understanding and capacity of students participating in the 82nd Field Study and Community Service (KKN) of UIN Raden Fatah Palembang, as service partners, in preparing and implementing quality community service programs. The method of implementing activities uses a service-learning approach, which is service-based learning that integrates direct experience in the community with academic reflection. Activities are carried out through workshops, interactive discussions, and assistance by Service Team. The results of the activities showed an increase in students' understanding of the basic principles of service and the preparation of work programs for KKN activities. The results of the activities and field findings indicate that students are better prepared and able to design KKN work programs in accordance with the needs of the local community. The implications of this activity strengthen the integration between the academic learning process and students' social responsibility in the context of the tri dharma of higher education. It is recommended that the service-learning approach continue to be developed and integrated systematically in the implementation of KKN to encourage the quality of service that is sustainable and has a real impact.